Circulating microRNAs as novel biomarkers for bone diseases – Complex signatures for multifactorial diseases?. (5th September 2016) - Hackl, Matthias; Heilmeier, Ursula; Weilner, Sylvia; Grillari, Johannes
Abstract: Biomarkers are essential tools in clinical research and practice. Useful biomarkers must combine good measurability, validated association with biological processes or outcomes, and should support clinical decision making if used in clinical practice. Several types of validated biomarkers have been reported in the context of bone diseases. However, because these biomarkers face certain limitations there is an interest in the identification of novel biomarkers for bone diseases, specifically in those that are tightly linked to the disease pathology leading to increased fracture-risk. MicroRNAs (miRNAs) are the most abundant RNA species to be found in cell-free blood. Encapsulated within microvesicles or bound to proteins, circulating miRNAs are remarkably stable analytes that can be measured using gold-standard technologies such as quantitative polymerase-chain-reaction (qPCR). Nevertheless, the analysis of circulating miRNAs faces several pre-analytical as well as analytical challenges. From a biological view, there is accumulating evidence that miRNAs play essential roles in the regulation of various biological processes including bone homeostasis. Moreover, specific changes in miRNA transcription levels or miRNA secretory levels have been linked to the development and progression of certain bone diseases. Only recently, results from circulating miRNAs analysis in patients with osteopenia, osteoporosis and fragility fractures have been reported. By comparing these findings to studies on circulating miRNAs in cellular senescence and aging or muscle physiology and sarcopenia, several overlaps were observed. This suggests that signatures observed during osteoporosis might not be specific to the pathophysiology in bone, but rather integrate information from several tissue types. Despite these promising first data, more work remains to be done until circulating miRNAs can serve as established and robust diagnostic tools for bone diseases in clinical research, clinical routine and in personalized medicine. Highlights: Circulating microRNAs meet the three key criteria of valuable biomarkers: measurability, validation and utility. The analysis of circulating miRNAs is rapidly advancing and clinical applications are on the verge of becoming reality. Careful pre-analytical planning and standardized protocols are required to generate bias-free and reproducible data. Several studies have addressed the utility of circulating miRNAs as biomarkers in bone and other multifactorial diseases. MicroRNA signatures could reflect skeletal as well as non-skeletal risk factors and accurately predict fracture-risk.